A method for the positioning and tracking of small moving particles. - Rees, N; Matthews, S; Yunus, K; Fisher, A; Compton, R (2009)
On the move: Electrochemistry has been used to detect and monitor the motion of a single 330 microm sphere in both time and space (see picture). The motion was recorded simultaneously by video and chronoamperometry, which showed an excellent correlation. The ability to fabricate electrode arrays capable of spatial resolution at the sub-micrometer scale opens the possibility of using this technique to monitor considerably smaller particles.